Implementation Of The Cooperative Performance Resilience Model Through Servant Leadership, Organizational Culture,And Social Capital At The Bintang 88 Muda Cooperative - Adriana Madya Marampa; Helba Rundupadang (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
The type of research used in this study is quantitative research. The sample in this study was 40 employees at the Bintang 88 cooperative. The scale used in this study was an ordinal scale. The data collection technique used in this study was purposive random sampling. The data analysis technique used in this study was SEM PLS. The results of this study indicate that there is a relationship between social capital and the resilience of cooperative performance, social capital influences the resilience of cooperative performance, servant leadership influences the resilience of cooperative performance.